Adaptation to an invasive host is driving the loss of a native ecotype. (1st October 2016) - Cenzer, Meredith L.
Abstract: Locally adapted populations are often used as model systems for the early stages of ecological speciation, but most of these young divergent populations will never become complete species. The maintenance of local adaptation relies on the strength of natural selection overwhelming the homogenizing effects of gene flow; however, this balance may be readily upset in changing environments. Here I show that soapberry bugs ( Jadera haematoloma ) have lost adaptations to their native host plant ( Cardiospermum corindum ) and are regionally specializing on an invasive host ( Koelreuteria elegans ), collapsing a classic and well‐documented example of local adaptation. All populations that were adapted to the native host—including those still found on that host today—are now better adapted to the invasive host in multiple phenotypes. Weak differentiation remains in two traits, suggesting that homogenization across the region is incomplete. This study highlights the potential for adaptation to invasive species to disrupt native communities by swamping adaptation to native conditions through maladaptive gene flow.